Volatilitas Harga Saham Industri Ekonomi Baru dan Non-Ekonomi Baru di Indonesia: Apakah Fenomena IPO keduanya berbeda? - Suhardjo, Iwan; Meliana, Meliana; Angeline, Angeline; Caroline, Caroline; Jaslyn, Jaslyn (Ekonomis: Journal of Economics and Business, 2024)
This research explores the influence of financial performance on the shares of companies conducting an Initial Public Offering (IPO) and analyzes the influence of leverage, company size, managerial ownership structure, and board educational background on share price volatility. This study is based on signal theory and focuses on new economy and non-new economy industries that conduct IPOs between 2021 and 2022. Using financial data from the Indonesia Stock Exchange (IDX) website, the population of e-commerce companies consists of 3 companies, while The sample of non-e-commerce companies consists of 12 companies. The research results show that leverage has a positive effect on stock price volatility.